The Accrual Anomaly: International Evidence - Pincus, Morton; Rajgopal, Shivaram; Venkatachalam, Mohan (The Accounting Review, 2007)
We consider stock markets in 20 countries to investigate whether the accrual anomaly (Sloan 1996), characterized by U.S. stock prices overweighting the role of accrual persistence, is a local manifestation of a global phenomenon.We explore whether the occurrence of the anomaly is related to country differences in accounting and institutional structures, and examine alternative explanations for its occurrence. We find stock prices overweight accruals in general, with accruals overweighting occurring in countries with a common law relative to a code law tradition. Using firmlevel data on a country-by-country basis, we document the occurrence of the anomaly in four countries, Australia, Canada, the U.K., and the U.S., and also in a sample of American Depository Receipts (ADRs) of firms domiciled in countries where we do not detect the anomaly. Using country-level data, we confirm the anomaly is more likely to occur in countries having a common law tradition, and also in countries allowing extensive use of accrual accounting and having a lower concentration of share ownership. Additional analyses reveal that earnings management and barriers to arbitrage best explain the anomaly.